Pemanfaatan Aplikasi Whatsapp sebagai Sarana Diskusi Antara Pengawas dan Guru Di Madrasah Binaan - Somantri, Tata (Jurnal Garasi Buku dan Obrolan Keilmuan, 2023)
Rapid technological advances in the field of communication have spawned many new innovations and ideas, ideas that aim to facilitate the process of human communication to be more effective. In the advancement of information technology, we can also connect with other people without any distance and time limitations. One of the innovations that facilitates the communication process is the cellular telephone or what is commonly shortened to the word handphone. The cellphones used today are very sophisticated, moreover cellphones now have various platforms such as Windows and Android. Mobile phones are usually also used as a means of connecting with other people by utilizing social media applications in the form of WhatsApp, Facebook, Twitter and many others. This research is a quantitative research. Sugiyono (2014) defines a descriptive method as a method used to analyze data by describing or describing the data that has been collected as it is without intending to make general conclusions or generalizations. Utilizing WhatsApp as a means of discussion between supervisors and teachers of Islamic religious education can be done by first creating a WhatsApp account, then proceed with creating a WhatsApp chat group, and then using the WhatsApp chat group as a means of discussion between supervisors and teachers of Islamic religious education. whether in the form of problem-solving discussions at school or exchange of information. The use of the WhatsApp application as a means of discussion between supervisors and Islamic religious education teachers as a whole based on a questionnaire filled out by Islamic religious education teachers is effective. To facilitate the exchange of information between supervisors and teachers under their guidance, it is better to use the WhatsApp application as a means of discussion. The use of the WhatsApp application is good that it can be further developed to perfect it.